Gender holocaust: The issue of female feticide - Pannu, Parveen (2016)
Indian census has always shown a gender imbalance. This marked gap between boys and girls, which has nationwide implications, is the result of decisions made at the most local level-the family. Decades of sex determination tests and female feticide have acquired genocide proportions. The article provides an overview of the mechanisms and consequences of these growing gender imbalances as observed today in India and its states through the complexities involved in the analysis of the sex ratio indicator covering women's survival and safety. It examines the extent of the trend towards more masculine populations, as well as its demographic determinants such as sex ratio at birth, mortality differentials, and the economic indicators. It is shown that this phenomenon is also characterised by distinctive regional and social variations within India.
Keywords: Women